2018
DOI: 10.1177/1932296818775755
|View full text |Cite
|
Sign up to set email alerts
|

Use of Blood Glucose Meters Featuring Color Range Indicators Improves Glycemic Control in Patients With Diabetes in Comparison to Blood Glucose Meters Without Color (ACCENTS Study)

Abstract: This study demonstrated that switching patients to BGMs featuring a CRI resulted in improvements in glycemic control compared to subjects using currently marketed BGMs that do not use a CRI. Registration: Clinicaltrials.gov NCT02929654 https://clinicaltrials.gov/ct2/show/NCT02929654.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 23 publications
1
43
1
1
Order By: Relevance
“…Certainly, enhancement in treatment satisfaction may play a critical role in increasing patient self-efficacy and commitment to therapy, thereby supporting in reaching long-term stable glycemic control, in addition to the minimization of the risk of diabetic complications [18]. More recently, diabetes technology has extended, and studies reported that technological improvements in glucometers are enhanced diabetes management and patient satisfaction [19,[23][24][25]. In this present study, we explored whether the smartLIGHT™ based BGM can impact the clinical characteristics and GMS in T2D patients over a period of time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Certainly, enhancement in treatment satisfaction may play a critical role in increasing patient self-efficacy and commitment to therapy, thereby supporting in reaching long-term stable glycemic control, in addition to the minimization of the risk of diabetic complications [18]. More recently, diabetes technology has extended, and studies reported that technological improvements in glucometers are enhanced diabetes management and patient satisfaction [19,[23][24][25]. In this present study, we explored whether the smartLIGHT™ based BGM can impact the clinical characteristics and GMS in T2D patients over a period of time.…”
Section: Discussionmentioning
confidence: 99%
“…It is well demonstrated that diabetes technology has expanded. Studies reported that technological improvements in glucometers, including SmartLIGHT™ glucometers, improve diabetes management and patient satisfaction due to on-screen glucose range information using a color range indicator [6,19,[23][24][25]27]. Studies also reported that a blood glucose meter that provides automatic on-screen glucose range information using a color range indicator significantly improved the ability of patients having T2D to classify blood glucose readings into low range, in the range, or high glycemic range [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Respondents strongly indicate (92.7%) that evidence is important in improving patient care and that it should inform choices relating to BGM. Recent evidence [ 2 ] shows that switching patients to BGM systems featuring color range indicators was associated with improvements in glycated hemoglobin levels compared to subjects using a wide selection of marketed BGM systems without color support [ 14 ]. Despite this, respondents support the assertion (78.5%) that there is a lack of evidence that more expensive BGM systems improve outcomes, suggesting that respondents may not be fully aware of recent innovations and published data.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, respondents support the assertion (78.5%) that there is a lack of evidence that more expensive BGM systems improve outcomes, suggesting that respondents may not be fully aware of recent innovations and published data. Data are available providing direct comparison between solutions that help the patient and HCP with insights and interpretation of the number versus traditional BGM [ 14 ].…”
Section: Discussionmentioning
confidence: 99%